The influence of ventilation systems on domestic gas appliances: An experimental study - Pinto, M. (2013)
Ventilation systems play an important role in the energy consumption of heating and cooling, defining hygrothermal conditions and air quality of dwellings. Among other functions, they are absolutely necessary to ensure oxygen levels needed for household combustion appliances. In Portugal in multifamily housing and with natural ventilation systems, installing a mechanical exhaust fan in every kitchen (decentralized ventilation) is common. In this paper, the impact of such a device is evaluated regarding the performance of a water heating appliance for heating the indoor environment or for domestic hot water (B-type gas appliance usually installed in the kitchen). The combination of natural or mechanical ventilation in the kitchen with the natural exhaust of the gas appliance’s combustion products were tested as well as the evaluation of critical conditions that lead to stopping the gas appliance safely or to reversing the combustion products in the respective exhaust duct. One of the main conclusions to be drawn is that in the case of mechanical exhaust in the kitchen simultaneously with the natural exhaust of the gas appliance’s combustion products, the kitchen’s exterior air inlet is a key device for ensuring proper exhaust of combustion products. In extreme situations, reduced air intake by other means or high extraction flows, they can prevent safely stopping the appliance or even reversing the flow of the combustion products. For this purpose, the maximum flow of mechanical exhaust should also be limited.